Willingness of visitors to pay for conservation of Giant Panda at Zoo Negara, Malaysia - Hashim, Muhamad Zharif Luqman (2018)
As a symbol of 40 years diplomatic relation between Malaysia-China, in year 2014 China Wildlife Conservation Association (CWCA) and Malaysian government have make a deal to loan two Giant Pandas. The arrival pair of Giant Panda has increased the number of visitors to the Giant Panda Conservation Centre (GPCC) in past three years. Facilities for Giant Panda are available at GPCC located in the Zoo Negara The general objective of this study was to estimate the conservation value of the Giant Panda at the Zoo Negara. Non-market valuation is used to compute the economic value of environmental resources. Even though several techniques can be used to evaluate the non-market commodities (environmental services), this study used the Contingent Valuation Method. This survey obtained an information in describing visitors’ willingness to pay for conservation of Giant Panda. A total of 335 respondents were selected among the visitors at GPCC. The results indicate that visitors to GPCC are willing to pay for the conservation of Giant Panda about RM24.88 per visit, while the conservation value was estimated at RM10.8 million for the year 2016. Findings also show that the factors influenced the WTP are monthly income, attractiveness of Giant Panda, visit experience in GPCC and perception on cost of visit to GPCC. This findings would also be helpful to assist the management authority to determine the admission fee and determining how much they can increase the entrance fee to visitors who enter the GPCC in the future.